Academic Senate Minutes 2002-03-07 - Academic Senate:::::::::
Report from Chair. Agenda and Minutes approved. Proposal for additional secretary duties failed. Faculty Governance Release time proposal approved. Reports from Vice President of Administration and Finance, Student Affairs, APC, EPC, SAC. Victor Garlin, President of CFA spoke for the Good of the Order on new tentative agreement for CFA. From the Floor, students presented a birthday card for Ruben Salazar to the Chair and made a statement concerning non-union labor remodeling Salazar Hall.